2009
DOI: 10.1111/j.1749-6632.2009.04019.x
|View full text |Cite
|
Sign up to set email alerts
|

AMP‐activated Protein Kinase and FoxO Transcription Factors in Dietary Restriction–induced Longevity

Abstract: Aging is regulated by modifications in single genes and by simple changes in the environment. The signaling pathway connecting insulin to FoxO transcription factors integrates environmental stimuli to regulate lifespan. FoxO transcription factors are directly phosphorylated in response to insulin/ growth factor signaling by the protein kinase Akt, thereby causing their sequestration in the cytoplasm. In the absence of insulin/growth factors, FoxO factors translocate to the nucleus where they trigger a range of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
89
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(98 citation statements)
references
References 35 publications
6
89
0
1
Order By: Relevance
“…In fact, molecular pathways analyzed, activation of the AMPK-FoxO axis was shown to be sufficient and required for the dietary restriction effects to occur on both healthspan and lifespan. 53 In particular, Greer and colleagues have shown that dietary restriction-dependent lifespan extension was suppressed in AMPK defective nematodes and significantly reduced in FoxO mutant strains. On the contrary, the long lifespan of insulin receptor mutant nematodes was further enhanced by dietary restriction.…”
Section: The Ampk-foxo Axis: Balancing Nutrient Sensing and Healthspamentioning
confidence: 99%
“…In fact, molecular pathways analyzed, activation of the AMPK-FoxO axis was shown to be sufficient and required for the dietary restriction effects to occur on both healthspan and lifespan. 53 In particular, Greer and colleagues have shown that dietary restriction-dependent lifespan extension was suppressed in AMPK defective nematodes and significantly reduced in FoxO mutant strains. On the contrary, the long lifespan of insulin receptor mutant nematodes was further enhanced by dietary restriction.…”
Section: The Ampk-foxo Axis: Balancing Nutrient Sensing and Healthspamentioning
confidence: 99%
“…p38 phosphorylates FoxO3a at Ser7 and promotes the nuclear translocation and activation of FoxO3a (Ho et al, 2012); JNK may repress the PI3K/Akt signal pathway, thereby activating FoxO3a indirectly, meanwhile, it may phosphorylayte FoxO proteins in a direct way (Sunters et al, 2006). FoxOs may also play a critical role in the regulation of energy homeostasis when phosphorylated by the AMP-activated protein kinase (AMPK) at six sites (Greer et al, 2009). In contrast to the effect of the above kinases on FoxOs, MST binds to FoxO3a and phosphorylates it at Ser207; however, the phosphorylation of this site promotes its nuclear accumulation and subsequently the expression of proapoptotic genes (Sanphui and Biswas, 2013).…”
Section: Overview Of Foxo Signaling Pathwaymentioning
confidence: 99%
“…NAD + -за-висимые деацетилазы SIRT1, HDAC1, 3, 4 активируют-ся при энергетическом голодании клетки; повышение их экспрессии продляет жизнь (Virtue, Vidal-Puig, 2008). AMPK, сенсор количества в клетке АМФ, способству-ет долголетию (Greer et al, 2009). Напротив, киназа TOR активируется при наличии аминокислот и ускоря-ет старение, ее ингибирование увеличивает продолжи-тельность жизни мышей (Harrison et al, 2009).…”
Section: генетика и эпигенетика старения и долголетияunclassified